Prevalence and distribution of developmental enamel defects in the primary dentition of pre-school children Prevalência e distribuição de defeitos de desenvolvimento de esmalte na dentição decídua de pré-escolares - Sandra Espíndola Lunardelli; Marco Aurélio Peres (Sociedade Brasileira de Pesquisa Odontológica, 2005)
Developmental defects of the enamel (D.D.E.) are changes in the deciduous dentition that have been little studied in Brazil, although they lead to aesthetic problems, dental sensitivity and may be predictors of dental caries. The objective of this study was to estimate the prevalence and distribution of D.D.E. in the deciduous dentition of pre-school children in the municipality of Itajaí, Santa Catarina, in 2003. A cross-sectional study was carried out with a sample of 431 children aged 3 to 5 enrolled in public day care centres. All of the teeth were examined and the enamel defects were assessed according to the Modified DDE Index (FDI, 1992). The prevalence of D.D.E. was 24.4% (CI 95% 20.3-28.5). Diffuse opacities were the most common defects found (17.9%), followed by hypoplasia (11.1%) and demarcated opacities (6.1%). The most affected teeth were the second molars (44.4%), followed by the first molars (23.5%). Defects were observed more frequently in the upper arch (58.2%). Assessing enamel hypoplasia separately, a prevalence of 15.1% (CI 95% 11.7-18.5) was observed, with the most affected teeth being the canines (33.6%) and second molars (33.6%). One quarter of the pre-school children presented enamel defects, with diffuse opacities being the most prevalent ones. No Brasil, os defeitos de desenvolvimento de esmalte (D.D.E.) são alterações pouco estudadas na dentição decídua apesar de acarretarem problemas estéticos, de sensibilidade dentária e serem fatores predisponentes da cárie dental. O objetivo deste estudo foi estimar a prevalência e distribuição de D.D.E. na dentição decídua de pré-escolares do município de Itajaí, Santa Catarina em 2003. Foi realizado um estudo transversal com uma amostra de 431 crianças de 3 a 5 anos de idade matriculadas em creches públicas. Todos os dentes foram examinados e os defeitos de esmalte foram avaliados segundo o "Modified DDE Index" (FDI, 1992). A prevalência de D.D.E. foi 24,4% (IC 95% 20,3-28,5). As opacidades difusas foram os defeitos mais encontrados (17,9%), seguidos das hipoplasias (11,1%) e opacidades demarcadas (6,1%). Os dentes mais acometidos foram os segundos molares (44,4%); seguidos pelos primeiros molares (23,5%). Os defeitos foram observados com maior freqüência na arcada superior (58,2%). Avaliando isoladamente as hipoplasias de esmalte, observou-se uma prevalência de 15,1% (IC 95% 11,7-18,5); sendo que os dentes mais atingidos foram os caninos (33,6%) e segundos molares (33,6%). Um quarto dos pré-escolares apresentou defeitos de esmalte, sendo que as opacidades difusas foram os mais prevalentes.